An Analysis of Gharar and Maisir in Claw Machine Games: A Review from the Perspective of Islamic Economic Law - Karisna, Anggi; Musthofa , M Arif; Sunarti, Zeni (CV. Civiliza Publishing, 2025)
Claw machine games have become an increasingly popular form of entertainment in various places, including shopping malls and cafés. However, despite their popularity, these games raise several concerns, particularly for children and teenagers. This study aims to analyze the practice of claw machine gaming and its impact from the perspective of Islamic economic law. A qualitative research method with a field study approach was used. Data were collected through observations and interviews with café owners, players, and parents of players at Café Kopi INJE, Tanjung Solok. The findings reveal that the game’s appeal lies in its element of challenge and luck, which encourages players to keep trying until they successfully win a prize. However, the game also increases consumerist behavior, triggers addictive effects, and can lead to psychological impacts such as frustration due to repeated failures. Furthermore, the game contains elements of uncertainty (gharar) and gambling (maisir), which contradict the principles of Islamic economic law. In the context of Indonesian law, luck-based games involving money may violate gambling regulations. The novelty of this study lies in its specific analysis of the implications of claw machine games from the perspective of Islamic economic law and their impact on the consumer behavior of children and teenagers. Therefore, stricter regulations are needed for luck-based games targeting children, along with early financial education. Educational and skill-based entertainment alternatives can serve as solutions to reduce the negative effects of these games